Obtaining of bilateral high voltage epitaxial p–i–n Si structures by LPE method - Vakiv, N. M.; Krukovsky, S. I.; Tymchyshyn, V. R.; Vas’kiv, A. P. (Technology and design in electronic equipment, 2013)
Silicon p–i–n-structures are usually obtained using conventional diffusion method or liquid phase epitaxy (LPE). In both cases, the formation of p- and n-layers occurs in two stages. This technological approach is quite complex. Moreover, when forming bilateral high-voltage epitaxial layers, their parameters significantly deteriorate as a result of prolonged heat treatment of active high-resistivity layer. Besides, when using diffusion method, it is impossible to provide good reproducibility of the process. In this paper, a technique of growing bilateral high-voltage silicon p–i–n-structures by LPE in a single process is proposed. The authors have obtained the optimum compounds of silicon-undersaturated molten solutions for highly doped (5.1018 cm–3) contact layers: 0.4–0.8 at. % aluminium in gallium melt for growing p-Si-layers and 0.03–0.15 at. % ytterbium in tin melt for n-Si-layers. Parameters of such structures provide for manufacturing of high-voltage diodes on their basis. Such diodes can be used in navigational equipment, communication systems for household and special purposes, on-board power supply systems, radar systems, medical equipment, etc.